(untitled) (CAHIERS MAGELLANES-NS, 2024)
Modern society requires an analytically thinking teacher who is able to instill analytical skills in his/her students; therefore, when preparing future teachers, in particular teachers of Russian literature, it is important to develop their analytical thinking. One of the ways of its formation can be the ability to work with didactic material, to choose the best textbooks for teaching certain lexical and grammatical topics. The purpose of the research is to develop the skills of critical analysis of linguistic and methodological literature in future teachers of literature. To achieve this goal, the article presents an example of the analysis of current textbooks on the Russian language for the study of incomplete syntactic constructions at school. Since incomplete sentences are a kind of deviation from the norms of constructing standard syntactic constructions in the Russian language, different points of view arise regarding their grammatical status, classification, and methods of analysis. Such disagreements lead to difficulties in their analysis and qualification in the university, and especially in the school curriculum. One of the controversial issues remains the issue of distinguishing between incomplete two-part sentences and one-part constructions. Incomplete one-member sentences are interesting and difficult to analyze, especially those with the omission of the main part. Insufficient attention is paid to the stylistic coloring of incomplete sentences in school practice of teaching the Russian language. In this regard, there was a need to analyze school textbooks. The analysis was aimed at identifying the features of the presentation of theoretical material, the typology of exercises and tasks for independent work, determining the positive and negative sides of different educational and methodological complexes in the Russian language. The experience of analysis presented in this article can serve as a model for working with educational material and will be useful primarily for a student philologist, a future teacher of Russian literature, for the formation of his analytical thinking, as well as a skilled teacher of literature in order to improve the effectiveness of teaching certain grammar topics.